Application of SWAN in Bangui Coast for potential energy harvesting - Arboleda, April Paul A.; Camelo, Jeane B. (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
Ilocos Norte was identified as one potential site for harvesting renewable ocean energy in the country. Known for its windmills and surfing spots, the coast of Ilocos Norte facing the West Philippine Sea possibly experiences wind generated wave that can be harvested using wave energy converters. As an alternative and renewable source of energy, there may be plans to build them in the future. Modeling software, like SWAN, can be used to aid in the planning process. This study aims to demonstrate such method of investigation, while producing energy density maps that can be used for future reference. Bathymetry data from the I :50000 topographic maps provided by the NAMRIA are first used to create a shapefile of the contour lines which is then interpolated by Blue Kenue to create the domain to be used by the model. Meanwhile, wind data from PAGASA is processed to create a wind rose diagram from which the most prominent wind is taken to be used for the simulation. The wind data is also used in hindcasting of the offshore waves that will be used as a boundary condition for the simulation. While it is preferable to make use of the physical processes that are presented by SWAN, limited availability of data proves to be a challenge making it not possible to do so. As a result, several assumptions are made and most variables are left on default. The output of the simulations are then post-processed with Blue Kenue and a spreadsheet editor to come up with a set of presentable figures. It is shown that the total power is comparable to the existing wind farm in the area if a large area of the coast is to be used for harvesting.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Ocean wave power; Ocean energy resources -- Philippines